Transient cooling episodes during Cretaceous Oceanic Anoxic Events with special reference to OAE 1a (Early Aptian) - Jenkyns, H (Royal Society, 2018)
The two major oceanic anoxic events of the Cretaceous, those of the early Aptian (OAE 1a) and the Cenomanian-Turonian boundary (OAE 2), registered some of the highest temperatures reconstructed for the Cretaceous Period, and are thought to be related to the input of volcanically derived carbon dioxide from one or more Large Igneous Provinces. Widely distributed deposition of marine organic matter, the hallmark of OAEs, and intensified silicate weathering in response to a globally accelerated hydrological cycle and/or reaction of seawater with freshly extruded basalt, are both potential mechanisms whereby the content of atmospheric carbon dioxide could have been drawn down to promote cooling, on the assumption that this potential effect was not offset by increased addition of this volcanically derived greenhouse gas. Reduction in the supply of such carbon dioxide, with deposition of organic matter and silicate weathering continuing at the same rate, could also have produced cooling. A transient fall in temperature and increase in marine dissolved oxygen levels is well documented for OAE 2, in the form of the so-called Plenus Cold Event or Benthic Oxic Event, associated with southward invasion of certain boreal faunas and an increase in many redox-sensitive and/or chalophilic elements in seawater caused by temporary loss of anoxic-euxinic sinks as basalt–seawater interaction continued apace. High-resolution studies of OAE 1a show at least three cooling episodes of probable global distribution, one of which (recorded in the stratigraphy of the so-called C4 Segment) is documented at high enough resolution to show correlation with an increase in carbon-isotope values that was probably due to a rise in the quantities of organic matter being buried globally, with consequent potential drawdown of atmospheric CO2 and/or reduction in volcanic input of this greenhouse gas. Both calcium- and lithium-isotope records suggest an increase in silicate weathering over the OAE 1a interval but current relatively low-resolution records cannot at present be tied to any one cooling episode, although the lowest Li-isotope values do derive from the C4 Segment. Evidence for re-oxygenation of the ocean during the transient cooling episodes of OAE 1a is meagre, due to the lack of suitable sedimentary archives, although a negative sulphur-isotope excursion in a Pacific shallow-water carbonate section, which can be interpreted as due to oxidation of pyrite and/or sulphur-rich organic matter in the global ocean, suggests that this phenomenon may also have been a feature of the C4 Segment. Further work is required to elucidate the similarities and differences between OAE 2 and OAE 1a but both phenomena are demonstrably global in reach and represent major disturbances to the carbon cycle with attendant effects on marine temperatures.